Innovative Methods Used In Life Safety Lessons (Eurasian Research Bulletin, 2023)
The use of various teaching methods is aimed at enhancing the cognitive activity of trainees in the course “Safety of human life activity”. The actions of the teacher, encourages students to strive to gain knowledge, this contributes to the creation of a positive attitude to academic work and activate their cognitive activity. The use of various methods in the educational process by teachers will allow them to successfully implement the requirements of the National Training Program for the formation of a new generation of personnel in the course “Safety of Human Vital Performance”.